1972
DOI: 10.1021/ja00768a018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a d7 iron system. Tetraphenylporphineiron(I) anion

Abstract: proteins is not probable unless the protein were attached to a pyrrole ring rather than being coordinated to iron(III).Acknowledgments. This investigation was supported in part by a grant from the Research Corporation. We are grateful to Barney Nist, University of Washington, for measuring the temperature-dependent nmr spectra and Professor G. Gerhold for supplying the computer program. We also thank Professor W. S. Caughey for helpful discussions.Characterization of a d7 Iron System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 1 publication
1
16
1
Order By: Relevance
“…5). By comparison with the well-known spectrum of five-coordinate low-spin Co(II) (d 7 ) porphyrins and with an early study of an electrochemically reduced ferroheme, 34 this signal can be assigned unambiguously to low-spin Fe(I)-P450cam trapped in the geometry of the parent Fe(II)-P450cam. The g tensor indicates that the odd electron on Fe is in the d z 2 orbital, with g along the heme normal.…”
Section: Ferrous-p450cam Complexes: Cryoreduction To Fe(i)mentioning
confidence: 82%
“…5). By comparison with the well-known spectrum of five-coordinate low-spin Co(II) (d 7 ) porphyrins and with an early study of an electrochemically reduced ferroheme, 34 this signal can be assigned unambiguously to low-spin Fe(I)-P450cam trapped in the geometry of the parent Fe(II)-P450cam. The g tensor indicates that the odd electron on Fe is in the d z 2 orbital, with g along the heme normal.…”
Section: Ferrous-p450cam Complexes: Cryoreduction To Fe(i)mentioning
confidence: 82%
“…From the very first times the catalytic or stoichiometric reactivity of doubly reduced Fe II porphyrin were investigated, until very recently, various spectroscopic techniques have indicated that the Fe II resonance form appears as largely predominant over the Fe 0 form (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Taking as an example the reduction of CO 2 to CO, the starting molecular reductant would be the Fe II resonance form of the doubly reduced Fe II porphyrin and the final product Fe II CO. From this perspective, the metal oxidation number seems to be invariant over the course of the reaction, and hence the ligand is not only noninnocent but also "redox active."…”
Section: Significancementioning
confidence: 99%
“…Because reduction of [FeTPP] can occur either at the metal or at the ligand, the exact nature of the electronic ground state of the reduced iron species [FeTPP] − and [FeTPP] 2– has long been controversial. A variety of spectroscopic studies, including Mössbauer, electron paramagnetic resonance (EPR), nuclear magnetic resonance (NMR), , X-ray, ,, UV/vis, ,,, and resonance Raman experiments have been published, partially supporting different electronic ground state formulations. Additionally, so far, resonance Raman experiments have been performed in solution, giving rise to solvent dependency of the electronic ground states. [FeTPP] and [FeTPP] − are even known to change their spin state upon axial ligation of solvent molecules .…”
Section: Introductionmentioning
confidence: 99%